Implementation of the Physica Education Curriculum and Physical Literacy of the College Students in China - Ding, Runxin (International Journal of Social Sciences and Public Administration, 2024)
With the rapid economic development and improved living standards in China, health and physical activity have gained increasing importance. Physical Education (PE) courses, as a vital component of higher education, play a crucial role in cultivating well-rounded talents with robust physical health. However, the current implementation of PE curricula faces numerous challenges, including inadequate university emphasis, imperfect facilities, weak faculty strength, monotonous teaching content, and outdated teaching methods, resulting in unsatisfactory physical literacy outcomes among college students. Meanwhile, factors such as changing lifestyles, academic and employment pressures, and misconceptions about sports further hinder the improvement of physical literacy. This study aims to explore the relationship between PE curriculum implementation and physical literacy cultivation among college students, propose targeted improvement suggestions based on assessments and analyses of the current status, and delve into the cultivation mechanisms and development patterns to optimize PE courses and enhance college students’ physical literacy. Theoretically, this research will enrich the theoretical framework of physical education; practically, it will promote the all-round development of college students, elevate their overall quality and competitiveness, and contribute to China’s modernization drive.